Isolation of Burkholderia sp. HQB-1, A Promising Biocontrol Bacteria to Protect Banana Against Fusarium Wilt Through Phenazine-1-Carboxylic Acid Secretion - Xu, Zhizhou; Wang, Mingyuan; Du, Jinpeng; Huang, Ting; Liu, Jianfu; Dong, Tao; Chen, Yinglong (Frontiers in Microbiology, 2020)
Fusarium wilt is a fungal devastating soil-borne fungal disease caused by Fusarium oxysporum f. sp. cubense (Foc). In recent years, some antifungal bacteria have been applied for the prevention and biocontrol of pathogenic fungi. In our study, athe bacterial strain HQB-1, isolated from banana rhizosphere soil, was cultured for investigation. It showed broad-spectrum antifungal activities against the representative phytopathogenic fungi including Fusarium oxysporum, Colletotrichum gloeosporioides, Botrytis cinerea, and Curvulatia fallax. The strain HQB-1 was identified as Burkholderia sp. by morphological, physiological, and biochemical testsexaminations, and it was confirmed by 16S rRNA gene sequence analysis. Among the metabolites produced by the strain, we identified The strain produced an antifungal compound which was identified confirmed to be phenazine-1-carboxylic acid (PCA) (C13H8N2O2) through ultraviolet, liquid chromatography quadrupole-time of flight mass spectrometer, and nuclear magnetic response. Furthermore, PCA exhibited the lowest minimum inhibitory concentration (MIC) against F. oxysporum (1.563 μg/ml) and yielded the highest MIC against C. gloeosporioides. Pot experiments showed that more thanapplication of 5 μg/ml or more of PCA could efficiently controlled banana wilt and promoted the growth of banana plants. These results suggested that Burkholderia sp. HQB-1, as an important microbial resource of PCA, is acould be a promising biological agent against plant wilt diseases and promoting banana growth.